Legal Regulation of Substitute Documents for Certificates of Indigency in Indonesian Legal Aid Administration: Normative Ambiguity, Accountability, and Comparative Lessons - Ni Putu Nathalia Dewi; Komang Widiana Purnawan (International Journal of Business, Law, and Education, 2026)
Access to legal aid is a constitutional and human-rights-based obligation of the state, particularly for indigent persons and vulnerable groups who face legal problems but lack the economic capacity to obtain professional legal assistance. Indonesian Law No. 16 of 2011 on Legal Aid and Government Regulation No. 42 of 2013 require proof of indigency, traditionally through a Certificate of Indigency (Surat Keterangan Miskin/SKM) issued by village or urban-village authorities. At the same time, Government Regulation No. 42 of 2013 allows applicants who do not possess an SKM to submit social assistance cards or “other documents” as substitutes. This article examines the regulatory construction of substitute documents, the legal consequences of the vague phrase “other documents,” and the accountability framework for officials, applicants, and legal aid providers involved in the issuance and use of such documents. It employs normative legal research with statutory, conceptual, and comparative approaches. The analysis shows that the open-ended formulation of substitute documents promotes administrative flexibility and access to justice, but also generates legal uncertainty, unequal implementation across regions, verification difficulties, risks of misuse, and potential administrative, civil, and criminal liability. Comparative analysis of England and Wales, the Netherlands, Australia, and Finland indicates that modern legal aid systems rely on nationally standardized eligibility criteria, means testing, integrated social-security or tax data, digital verification, and audit mechanisms. The article argues that Indonesia should harmonize legal aid regulation with social welfare, civil registration, public administration, and personal data protection regimes by establishing a national list of acceptable substitute documents, creating a tiered verification model, integrating legal aid eligibility with the National Single Socio-Economic Data (DTSEN), and strengthening accountability safeguards. Such reform is necessary to ensure that administrative requirements function as instruments of inclusion rather than barriers to justice.